CLINICAL CHARACTERISTICS OF THE TYPES OF DAILY BLOOD PRESSURE PROFILES IN PATIENTS WITH ARTERIAL HYPERTENSION DEPENDING ON THE SELECTED ABPM INDEX - O. V. Petrenko; О. V. Martynenko; M. I. Yabluchansky (Journal of V. N. Karazin Kharkiv National University: Series Medicine, 2016)
The frequency characteristics of the clinical signs of arterial hypertension (AH) according to the daily profile type of systolic (SBP), diastolic (DBP) and pulse (PP) blood pressure were studied. The data showed a significant difference in the frequency of occurrence of AH clinical signs, depending on the type of daily profile of SBP, DBP, and PP. It was concluded that in patients with AH determination only SBP daily profile of is not enough, it's necessary to take into account the types of DBP and PP daily profiles also.